2007
DOI: 10.1093/treephys/27.12.1671
|View full text |Cite
|
Sign up to set email alerts
|

Stored water use and transpiration in Scots pine: a modeling analysis with ANAFORE

Abstract: We estimated daily use of stored water by Scots pine (Pinus sylvestris L.) trees growing in a temperate climate with the ANAFORE model (ANAlysis of FORest Ecosystems) and compared the simulation results with sap flow measurements. The original model was expanded with a dynamic water flow and storage model that simulates sap flow dynamics in an individual tree. ANAFORE was able to accurately simulate diurnal patterns of measured sap flow under microclimatic conditions that differ from those of the calibration p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 75 publications
0
47
0
2
Order By: Relevance
“…This response has been previously linked to soil moisture, VPD, and plant physiology Novick et al, 2014;Unsworth et al, 2004;Verbeeck et al, 2007b;Zhang et al, 2014]. Red oaks had the largest mean absolute hysteresis in the treatment plot, the second largest mean absolute hysteresis in the control plot, and the largest mean relative hysteresis in both plots.…”
Section: Red Oakmentioning
confidence: 55%
“…This response has been previously linked to soil moisture, VPD, and plant physiology Novick et al, 2014;Unsworth et al, 2004;Verbeeck et al, 2007b;Zhang et al, 2014]. Red oaks had the largest mean absolute hysteresis in the treatment plot, the second largest mean absolute hysteresis in the control plot, and the largest mean relative hysteresis in both plots.…”
Section: Red Oakmentioning
confidence: 55%
“…To model water fluxes, it integrates a dynamic water flow model in a process based transpiration model as described in a companion paper by Verbeeck et al (2007). Stomatal aperture, sap flow, photosynthesis (Farquhar et al, 1980) and transpiration (Penman, 1948;Monteith, 1965) are simulated on a half-hourly basis.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Several authors found that the contribution of internal water to transpiration is not a constant in the water budget of trees (Loustau et al, 1996;Köstner et al, 1998;Zweifel et al, 2005;Verbeeck et al, 2007), but changes dynamically from day to day. To determine the complete water balance of a forest ecosystem and its dynamics, it is therefore important to know which factors influence the use of stored water.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations